Emerging trends in mathematics assessment practices in Southeast Asia - Puspitaningtyas, Apriliana Retno; Nurhasanah, Farida; Indriati , Diari (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2025)
Assessment in education has shifted from summative to formative models in recent decades, with technological advancements facilitating flexible implementation anytime and anywhere. Stemming from this phenomenon, this study aims to identify the trends in mathematics learning assessment in Southeast Asia through a systematic literature review (SLR) utilizing the PRISMA protocol. Articles were collected from the Scopus and ERIC databases, yielding an initial 1533 articles, which were then filtered to 39 final articles for analysis. The results indicate that Assessment for Learning is the most frequently studied assessment topic in the context of mathematics assessment in Southeast Asia (15 articles), with quantitative research dominating the methodologies employed (18 articles). The most prominent research objective is assessment for evaluation purposes (nine articles). Furthermore, junior high school and undergraduate levels are the most researched educational levels (10 articles each). Lastly, the Quizizz application is the most frequently discussed assessment practice in mathematics classrooms in Southeast Asia (two articles). The practical implication of these findings highlights the need for a study on the topic of assessment as learning in mathematics education. More effort is needed to make prospective teachers and teachers of mathematics utilize technology in assessment in mathematics learning.